Peningkatan Proses Pembelajaran Tematik Terpadu Dengan Menggunakan Model Discovery Learning Di Kelas IV Sekolah Dasar - nailul khaira; Harni Harni; Yalvema Miaz (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research was intended to describe the improvement of the integrated thematic learning process by using by using the Discovery Learning model with the rich theme always save energy  Negeri 13 Bukit Apit Puhun Kec. Guguk Panjang Bukittinggi City. The approach used in this Classroom Action Research is a qualitative and quantitative approach implemented in two cycles. The subjects of this study were teachers and 36 students of grade IV SDN 13 Bukit Apit Puhun Kec. Guguk Panjang Bukittinggi City. The results showed that in the first cycle the average RPP score was 60,10% (good), the average teacher aspect was 65,62% (good), the average student aspect was 65,62% (good), the students' Aspects of attitude, knowledge, and skills with an average of 72.07 with a conversion value of 3.16 (B +). In the second cycle the average RPP assessment is 88,85% (very good), the average teacher aspect is 89,02% (very good), the average student aspect is 89,02% (very good), the students' Attitude, knowledge, and average skills 80,54 with conversion value of 3.41 (B +). From the results of the study can be concluded that by using the model of Discovery Learning can improve the integrated thematic learning process in class IV SD Negeri 13 Bukit Apit Puhun  Bukittinggi